Case Report: Efficacy of Pyrotinib in ERBB2 Amplification Pulmonary Adenoid Cystic Carcinoma - Tang, Zhongben; Lin, Feng; Xiao, Jiarong; Du, Xiaojun; Zhang, Jian; Li, Sini; Tang, Gongshun; Chen, Chen; Li, Jian (Frontiers in Oncology, 2021)
Primary pulmonary adenoid cystic carcinomas are salivary tumors that are low-grade malignant and prone to recurrence and metastasis. Surgery is currently the main treatment, but there is no standard with regard to postoperative adjuvant therapy. Adenoid cystic carcinoma is more sensitive to radiotherapy and patients benefit less from chemotherapy, but few studies have focused on targeted therapy, and their conclusions are inconsistent. With respect to primary pulmonary adenoid cystic carcinoma, large-scale studies cannot be conducted due to its low incidence, and studies on the targeted therapy of it are very scarce. A few case reports indicate that targeted therapy can be effective however, suggesting that it may be a good option. The current report is the first on the occurrence of human epidermal growth factor receptor 2 amplification in pulmonary adenoid cystic carcinoma. The patient was treated with pyrotinib for 6 months and achieved stable disease.